Nanorough Surface of Fibronectin Grafted Bioactive Zirconia Dental Implants by Using Glow Discharge Plasma Promotes Osseointegration in a Rabbit Model - Aung LM; Renn TY; Lin JCY; Salamanca E; Wu YF; Pan YH; Teng NC; Huang HM; Sun YS; Chang WJ (International Journal of Nanomedicine)
Lwin Moe Aung,1 Ting-Yi Renn,1 Jerry Chin-Yi Lin,1,2 Eisner Salamanca,1 Yi-Fan Wu,1,3 Yu-Hwa Pan,1,4,5 Nai-Chia Teng,1,6 Haw-Ming Huang,1 Ying-Sui Sun,7 Wei-Jen Chang1,8 1School of Dentistry, College of Oral Medicine, Taipei Medical University, Taipei, Taiwan; 2Department of Oral Medicine, Infection and Immunity, Harvard School of Dental Medicine, Boston, MA, USA; 3Department of Biomedical Engineering, Ming-Chuan University, Taoyuan, Taiwan; 4Department of Dentistry, Chang Gung Memorial Hospital, Taipei, Taiwan; 5School of Dentistry, College of Medicine, China Medical University, Taichung, Taiwan; 6Department of Dentistry, Taipei Medical University Hospital, Taipei, Taiwan; 7School of Dental Technology, College of Oral Medicine, Taipei Medical University, Taipei, Taiwan; 8Dental Department, Shuang-Ho Hospital, Taipei Medical University, Taipei, TaiwanCorrespondence: Wei-Jen Chang; Ying-Sui Sun, Email cweijen1@tmu.edu.tw; yingsuisun@tmu.edu.twPurpose: Nano-engineering techniques have significantly enhanced the various aspects of dentistry, with notable advancements, especially in dental implant surface modification. Dental implants are among the most significant and highly successful developments in contemporary dentistry. The use of nanotechnology for surface modification of zirconia ceramic implant increases interaction with surrounding bone cells, and ultimately leading to increase osseointegration.Materials and Methods: Glow discharge plasma was utilized to graft allylamine and fibronectin nanoproteins onto the surface of zirconia implants. A total of 18 implants were placed in right and left femurs of nine New Zealand rabbits. Implant stability test (IST), 3D bone reconstruction and micro-CT (μCT) analysis, bone-implant contact (BIC) from histomorphometry analysis, and osteogenic gene expression were analyzed after scarification at 4, 8, and 12 weeks.Results: IST results demonstrated a significant secondary stability gain at the end of 12 weeks. The surface-treated group obtained a gradual increase in marginal bone level. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) analysis revealed increased expression of osteogenic genes of alkaline phosphatase (ALP) and transcription factor SP7 (SP7) biomarkers at 4 weeks. Osteoprotegerin (OPG) expression increased at 8 weeks, while runt-related transcription factor 2 (RUNX2), collagen 1A1 (COL1), bone sialoprotein (BSP), and receptor activator of nuclear factor κ B (RANK) exhibited the highest expression at 12 weeks. Importantly, histomorphometric analysis of BIC indicated that new bone formation was significantly higher in the A50F10 group compared to the control group at 12 weeks (P < 0.001).Conclusion: Based on the above findings, we conclude that the nanorough zirconia implant surface grafted with fibronectin nanoproteins prominently stimulated cellular activity and improved osseointegration properties. These results evidence its potential for future applications in dental implant surface modifications. Keywords: nano-roughness, surface modification, glow discharge plasma, zirconia implants, osseointegration, fibronectin